Perancangan User Experience Aplikasi Mobile Daily Goals Management menerapkan Sistem Accountability Partner dengan Metode Human-Centered Design - Ahmad Kholish Fauzan Shobiry; Hanifah Muslimah Az-Zahra; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
The industrial revolution 4.0 has an impact on students' readiness in carrying out the learning process, readiness in the learning process is vital in the learning system. Student motivation is an indicator of readiness in dealing with existing learning methods. However, low motivation often occurs because there is no initiative and consistency. Student motivation can be prepared through goal-setting training to overcome these problems. Goal-setting training is able to increase student learning motivation and spur increased productivity. Thus, this study aims to assist learning readiness through goal-setting training as well as the potential for increased productivity in the education sector. The addition of the application of the accountability partner system can increase individual performance in completing a goal by 95%. The application design uses the human-centered design method through several stages of analysis aimed at producing a solution design that is easy to understand and answers user problems. The design evaluation process for the daily goals management mobile application uses usability testing with an assessment of the SUS questionnaire. The design test results obtained an effectiveness value of 97.85%, an efficiency level of 93.70%, and the satisfaction aspect reached 79 out of 100. Based on these values, the benchmark design of the user experience mobile daily goals management application is included in the grade B category, good adjective rating, and acceptable category.